1979
DOI: 10.1149/1.2129238
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of Metals in Fluidized Bed Electrodes: Part I . Mathematical Model

Abstract: A mathematical model is presented to describe the behavior of fluidized bed cathodes when employed in the electrodeposition of metals from solution. Principal results are the effect of electrode and electrolyte resistivity on cell voltage, power consumption, operability, and bed effectiveness. The model applies to a multicomponent electrolyte and allows for the presence of oxid izin.g agents in the electrolyte. Computed results also include current efficleneles.* Electrochemical Society Active Member. 1 Presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The higher oxygen removal can be explained by the fact that the resistivity decreases with the increase of the electrolyte concentration. A study by Sabacky and Evans 27 showed that efficiency and power consumption in a porous electrode cell depends also on the resistivity of the electrolyte and predicted inefficient utilization of bed surface at high electrolyte resistivity.…”
Section: Resultsmentioning
confidence: 99%
“…The higher oxygen removal can be explained by the fact that the resistivity decreases with the increase of the electrolyte concentration. A study by Sabacky and Evans 27 showed that efficiency and power consumption in a porous electrode cell depends also on the resistivity of the electrolyte and predicted inefficient utilization of bed surface at high electrolyte resistivity.…”
Section: Resultsmentioning
confidence: 99%
“…As already indicated, anodic zones can form in the moving bed cathode if the current density is not sufficiently high. Sabacky and Evans [36] were among the first to introduce the concept of an effectiveness factor in a fluidized bed electrode as the ratio of total deposition rate to the rate when bed and electrolyte exhibit zero resistance. Similarly, Scott [37] defined an effectiveness factor in a particulate bed as the fraction of electrode area that effectively contributes to electrodeposition.…”
Section: Discussionmentioning
confidence: 99%
“…16 where the variation of the timeaveraged overpotential with position is displayed. Theoretical models for porous electrodes, e.g., that of Newman and Tobias (15), and_for fluidized bed electrodes, e.g., that of Sabacky and Evans (16), have predicted the corresponding U-shaped distribution of local reaction rate. Experimental confirmation of this variation of deposition rate (in copper electrodeposition experiments) with an inactive zone in the middle of the bed has been provided by Masterson and Evans (17).…”
Section: Resultsmentioning
confidence: 99%